Effect of lactic acid bacteria isolated from raw and fermented camel milk on chemical composition and nutrient digestibility of sugarcane bagasse in vitro (Acta Scientiarum. Animal Sciences, 2026)
The purpose of this study was the isolation of the lactic acid bacteria from camel milk and its use in processing of sugarcane bagasse (SB). For isolation and purification of lactic acid bacteria, the raw and fermented camel milk samples were cultured on De Man–Rogosa–Sharpe agar (MRS) culture, and after incubation, the colonies were cultured on liquid MRS culture and again on MRS agar. After gram staining, bacterial DNA extraction and 16S rRNA genome sequencing were performed. The isolated bacterial culture grown in liquid MRS medium was utilized to process SB as described below: SB with no processing (control), SB processed with lactic acid bacteria isolated form fermented camel milk (FCM), (SB-FCM) and SB processed with lactic acid bacteria isolated form raw camel milk (RCM), (SB-RCM). Results indicated that bacteria isolated from RCM and FCM were 99.33 and 99.42% similar to Enterococcus durans and Limosilactobacillus reuteri, respectively. Isolated bacteria had no significant effect on the dry matter of SB (P < 0.05). The treatments decreased the amount of ash, neutral detergent fiber (NDF) and acidic detergent fiber (ADF) and increased the amount of organic matter (OM) in SB (P < 0.05). The results of the gas production test showed that the actual digested OM, microbial mass production, PF, potential and gas production were similar among treatments (P > 0.05). The NDF and ADF digestibility were not different between treatments (P > 0.05). Therefore, Enterococcus durans and Lactobacillus reuteri, isolated from RCM and FCM, improved the OM content of SB while decreasing its NDF and ADF concentrations. Therefore, the isolated bacteria have the potential to be used as additives to enhance the digestion of fibrous components in SB, making it more suitable for ruminant feed.